THE EFFECT OF SYNTHETIC ZEOLITES ON SENSITIVITY AND STABILITY OF URIC ACID BIOSENSOR USING CYCLE VOLTAMETRY METHOD - Iza Faizah; Dwi Puryanti; Afdhal Muttaqin (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
The synthesis of synthetic zeolite modified biosensor material has been carried out to detect uric acid. This study aims to look at the effect of synthetic zeolite on uric acid biosensor material on sensor stability and sensitivity. The biosensor was use to measure uric acid using uricase produced Lactobacillus plantarum. Modification of biosensor material using synthetic zeolite content of Sodalit is added in a mixture of graphite and paraffin. Carbon paste electrode (EPK) was made with graphite and paraffin comparison 70 mg : 30 mg, while zeolite modified carbon paste electrode (EPKZ) with graphite, paraffin and zeolite comparison 50 mg: 30 mg: 20 mg. In each electrode, 7.5 Î¼l of L.plantarum pellet (EPKZLP) was dropped. Electrode performance testing was carried out using Cyclic Voltammetry. Modification results affect biosensor performance such as sensitivity and stability. The highest current is produced by EPKZLP with a current range of 0.0143 - 0.0592 mA. The best sensitivity is produced in EPKZLP with a value of 0.031 mAcm-2mM-1. The best stability was found in EPKZLP with a percentage of stability on day 14 was 30.9%. The average standard deviation generated in this study is 0.0024 mA with a relative error value was 7.8%. Addition of zeolite to biosensor material produced in this study has met several criteria to be used as a sensor. Keywords: uric acid biosensor, zeolite, sodalit, sensitivity, stability.